2011
DOI: 10.1177/0093854811412170
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Sequences in Police Interviews and the Importance of Order and Cultural Fit

Abstract: This study introduces the concept of strategic sequences to police interviews and concentrates on the impact of active listening behavior and rational arguments. To test the authors' central assumption that the effectiveness of strategic sequences is dependent on cultural fit (i.e., the match with the cultural background of suspects), young people participated in virtual police interviews. Study 1 demonstrated that contrast sequences accentuating rational rather than relational behavior were found to be effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Lee, Adair, and Seo (2013) demonstrated that negotiators who engaged in cultural perspective taking prior to Uncertainty Avoidance in Negotiation 7 interaction claimed more value from the negotiation than those who did not. Similarly, Beune, Giebels, Adair, Fennis, and Van der Zee (2011) found that behavioral sequences accentuating rational rather than relational behavior were more effective in eliciting information from perpetrators with a cultural preference for direct communication compared to perpetrators with a preference for indirect context-orientated communication. Contextualizing these findings to the current research suggests that alignment will occur more naturally in interactions where police negotiators are interacting with perpetrators from their own culture.…”
Section: Culture and Communication Alignmentmentioning
confidence: 91%
See 1 more Smart Citation
“…Lee, Adair, and Seo (2013) demonstrated that negotiators who engaged in cultural perspective taking prior to Uncertainty Avoidance in Negotiation 7 interaction claimed more value from the negotiation than those who did not. Similarly, Beune, Giebels, Adair, Fennis, and Van der Zee (2011) found that behavioral sequences accentuating rational rather than relational behavior were more effective in eliciting information from perpetrators with a cultural preference for direct communication compared to perpetrators with a preference for indirect context-orientated communication. Contextualizing these findings to the current research suggests that alignment will occur more naturally in interactions where police negotiators are interacting with perpetrators from their own culture.…”
Section: Culture and Communication Alignmentmentioning
confidence: 91%
“…Similar patterns have been found in the field of police interviews. Beune et al (2011) found that individualistic Uncertainty Avoidance in Negotiation 8 perpetrators are more cooperative when confronted with rational rather than relational strategies, with a reversed pattern for collectivistic perpetrators.…”
Section: Legitimizing Formality and Alignmentmentioning
confidence: 95%
“…Third, students have been used successfully before in studies in the suspect interview (cf. Beune, Giebels, Adair, Fennis, & Van der Zee, 2011;Russano, Meissner, Narchet, & Kassin, 2005) and crisis negotiation domain (cf. Giebels, Oostinga, Taylor, & Curtis, 2017) with results corresponding to those found in field studies.…”
mentioning
confidence: 99%
“…Negotiators can also specify their strategy beforehand when they know the cultural background of the perpetrator. Ellen's work shows that the cultural background of the perpetrator determines to a great extent whether or not the use of certain tactics is effective (Beune, Giebels, Adair, Fennis, & Van der Zee, ; Giebels, Oostinga, Taylor, & Curtis, ; Giebels & Taylor, ).…”
Section: Working With Ellen: the Interaction Between Theory And Practmentioning
confidence: 99%